A critical review on role of biofertilizers in enhancing the productivity of oilseed crops: A CRITICAL REVIEW ON ROLE OF BIOFERTILIZERS IN ENHANCING PRODUCTIVITY OF OILSEED CROPS - M JAYAKUMAR; A SOLAIMALAI; K BASKAR (Journal of Oilseeds Research, 2021)
Oilseeds are mainly cultivated as rainfed crop with poor input resources. This will have impact on plant health particularly plant nutrition, pests, diseases and weeds. Further, this problem is region specific and depends on the soil condition and climate. Biofertilizers are the products containing different types of beneficial microorganisms. Applications of biofertilizers have definite advantage over chemical fertilizersin oilseed crops. Chemical fertilizers supply nitrogen in higher concentrations whereas bio-fertilizers provide nutrients in small amounts in a sustained way. In addition to nutrients, certain growth promoting substances like hormones, vitamins, amino acids, etc are made available to plants. Bio-fertilizers application will have impact on organic agriculture, reduction of environmental pollution, soil health improvement and reduction in input use for oilseed crops. Current soil managementstrategies are mainlydependent on chemical based fertilizers, which caused a serious threat to human health and environment. The exploitation of beneficial microbes as a biofertilizer has become important in agriculture sector for their potential role in food safety and sustainable crop production. The eco-friendly approaches inspire a wide range of application of plant growth promoting rhizobacteria (PGPRs), endo and ectomycorrhizal fungi and many other useful microscopic organismsled to improved nutrient uptake, plant growth and plant tolerance to abiotic and biotic stress. The knowledge gained from the literatures appraised herein helped us to understand the physiological bases of biofertlizers towards sustainable agriculture in reducing problems associated with the use of chemicals fertilizers in oilseeds production.